Development of Science E-Flipbook Integrated Illegal Sand Mining on River Basin to Improve Environmental Care Attitude - Shobhi Al-Ghifari Azhary; I Gusti Putu Suryadarma; Puspa Indah Devitasari; Kuswanto Kuswanto (Universitas Muhammadiyah Mataram, 2020)
The aim of this research is to produce a valid e-flipbook on science learning content for water pollution that integrated with illegal sand mining activities in a river basin to enhance environmental care attitude. The research method used was research and development with ADDIE models that are limited to the developing stage. The research sample consisted of 20 seventh grade students of junior high school. The average validation resulted by media expert is 3,5 and content expert is 3,6 with very good category, the result of validation by science teacher is on average 3,6 with very good category and peer reviewer obtained an average value of 3,7 with very good category, the results of validation by 20 students obtained an average value of 3,7 with very good categories. Research data were analyzed and interpreted using descriptive analysis. Based on the results of development and validation, this e-flipbook can be concluded valid and can be applied in learning. This research is important because it uses technology and raises issues about environmental problems